2022
DOI: 10.1021/acsanm.1c04496
|View full text |Cite
|
Sign up to set email alerts
|

Red-Emitting Silver Nanoclusters for Dual-Mode Detection of Cu2+ and Vitamin B12 in Living Cells

Abstract: Biomolecule-stabilized metal nanoclusters (MNCs) exhibit enormous potential as unique luminescent materials in various applications. However, synthesis of highly stable and bio-friendly fluorescent MNCs is still a challenge. Here, we report a facile synthesis of red-emitting silver nanoclusters (LYS–AgNCs) within a dithiothreitol-reduced lysozyme (LYS) scaffold. The nanoclusters exhibit a uniform size distribution, excellent water solubility, and superior photoluminescence properties featuring a quantum yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 64 publications
0
8
1
Order By: Relevance
“…Thus, from the MALDI-TOF analysis, it could be concluded that each tryptophan scaffolded Cu NCs were composed of less than 5 atoms. Although this result deviates from the cluster size predicted by Jellium Model [69,70], nanoclusters with a lesser number of atoms with emission in the longer wavelength are not uncommon [62,71,72].…”
Section: Green Emitting Trp-cu Nccontrasting
confidence: 82%
“…Thus, from the MALDI-TOF analysis, it could be concluded that each tryptophan scaffolded Cu NCs were composed of less than 5 atoms. Although this result deviates from the cluster size predicted by Jellium Model [69,70], nanoclusters with a lesser number of atoms with emission in the longer wavelength are not uncommon [62,71,72].…”
Section: Green Emitting Trp-cu Nccontrasting
confidence: 82%
“…The deconvoluted XPS peaks of C 1s were at 284.4, 285.2, 286, 287.9, and 289.8 eV, which were linked to C–C/CC, C–N, CN, CO, and O–CO, respectively (Figure e). , The high-resolution N 1s spectrum revealed four different kinds of N-functionalities: pyridinic-N (398.8 eV), pyrrolic-N (399.5 eV), amino-N (400.2 eV), and graphitic-N (401.7 eV) (Figure f). , Similarly, the deconvoluted O 1s XPS spectrum exhibited well-defined peaks at 530.8, 531.3, 532.1, 533, and 533.8 eV corresponding to the O–C/C–O–C, OC–N, CO, C–OH, and O–CO bonds, respectively (Figure g). , The exact percentage of contribution calculated from the XPS analysis is presented in Table S1. The Fourier transform infrared (FTIR) spectra (Figures S1, and h) showed peaks at 1612, 1512, 1434, 1364, and 1290 to 1140 cm –1 corresponding to the stretching vibrations of the amide linkage (NH–CO), CN, CC, N–H, and C–O-related functional groups. ,,, The combined XPS and FTIR analyses ascertained the chemical composition and functionalities of the D-CD surfaces. Furthermore, the D and G bands in the Raman spectra (Figure i) were at 1371 and 1569 cm –1 , respectively, with the D/G band intensity ratio at 1.08, suggesting effective Raman active surface sites.…”
Section: Resultsmentioning
confidence: 99%
“…The Fourier transform infrared (FTIR) spectra (Figures S1, and 1h) showed peaks at 1612, 1512, 1434, 1364, and 1290 to 1140 cm −1 corresponding to the stretching vibrations of the amide linkage (NH−C�O), C�N, C�C, N−H, and C−O-related functional groups. 40,44,47,48 The combined XPS and FTIR analyses ascertained the chemical composition and functionalities of the D-CD surfaces. Furthermore, the D and G bands in the Raman spectra (Figure 1i) were at 1371 and 1569 cm −1 , respectively, with the D/G band intensity ratio at 1.08, suggesting effective Raman active surface sites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the past few years, researchers have put tremendous effort on the design of various MNC-based luminescent probes, [31][32][33][34] such as PL-tunable ones from the visible to near infrared region in the first and second windows (NIR-I and NIR-II), 3,31 those engineered with targeted functions for specific cells/tissues/organs, 35 and those holding theranostic attributes. 36 Such a plenty of MNC-based luminescent probes substantially promoted the realization of their broad applications ranging from cell imaging, 37 disease theranostics, 38 to in vivo metabolism assessment, 39 which indeed addressed many challenging issues in the biomedical field. However, there are still several pending problems in bioimaging: (1) while many MNCs have been demonstrated to be capable in luminescence imaging of cells/tissues/organs, the advancement in subcellular organelle imaging is very slow, which is due to the lack of appropriate MNCs with targeted functions for specific subcellular organelles (e.g., mitochondria and lysosomes); (2) luminescence imaging of the brain is very challenging because it is difficult for luminescent probes to approach the brain due to the protection of the blood brain barrier (BBB).…”
Section: Introductionmentioning
confidence: 99%